PEMAHAMAN KONTEKS BUDAYA DALAM INTERPRETASI TEKS BAHASA INGGRIS BIDANG EKONOMI: KAJIAN LITERATUR UNTUK MAHASISWA EKONOMI PEMBANGUNAN - Adys, Himaya Praptani (Media Inovasi Pendidikan dan Pembelajaran, 2025)
This research examines the importance of understanding cultural context in comprehending English-language economic texts for Development Economics students through a systematic literature review approach. Economic globalization demands that students not only master English technically but also understand the cultural dimensions underpinning economic concepts. This study analyzes 35 articles from reputable databases to identify gaps in the understanding of cultural context within economic English learning. The results indicate that an understanding of cultural context significantly enhances competency in interpreting economic texts, cross-cultural business decision-making, and the capacity for development policy analysis. The developed theoretical framework integrates the theory of intercultural communicative competence with the English for Specific Purposes approach. The findings provide practical implications for the development of a culturally responsive curriculum and learning strategies for economic English. Cultural Context, Economic English, Development Economics, intercultural Competence, Literature Review